A systematic review of treatment approaches for compulsive exercise among individuals with eating disorders. Issue 4 (4th July 2022) - Hallward, Laura; Di Marino, Annissa; Duncan, Lindsay R.
ABSTRACT: Individuals with eating disorders often experience compulsive exercise which, if left untreated, can lead to longer treatment and worsened symptoms. Compulsive exercise must be addressed within eating disorder treatment to help individuals establish a healthy relationship with exercise. However, there are currently no standardized guidelines for treating compulsive exercise or a consensus on which forms of treatment are most effective. Therefore, the purpose of this review was to examine interventions that address compulsive exercise and their impact on treating compulsive exercise among individuals with eating disorders. A systematic review of the literature was conducted. Eleven studies testing treatments for compulsive exercise were included in this review. Participants were diagnosed with anorexia nervosa, bulimia nervosa, or EDNOS, and a small portion had BED. Improvements in compulsive exercise and eating psychopathology were observed across all studies. The interventions focused on exercise psychoeducation and often incorporated exercise sessions. The findings highlight the positive impact of treating compulsive exercise, suggesting it should be a standard component of eating disorder treatment. Future studies should examine differences in treatment approaches and outcomes specific to each eating disorder, and specific to males. More consistency across studies in the conceptualization and measurement of compulsive exercises is also needed.